(3QSGdI GdQHY GdeLfMs - (3GHf GdSQGL,J (B726 (3g` s
(3ChdgG (B:s
(3HYO GdHSedI hGdMeO (B: (3GdHGH ai eYQaI LjH GdbhS hbhS GdLjH s
(3BNQgG (B:s
(3bGFOg EPG fbUJ MUg GdaLQ ef fUa bhS Gddjd hROJ eG Hbi bag OQLg cGf GdOGjQ ef Gdadc ef GdRhGd Edi hbJ WdhY GdaLQ s
(3Vef eLehY , JQJjHgG (B: (3ef U (B1 - (3U(B4s
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B126 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B43 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3ejbGJ (B138) s
Keywords: (3Gdadcs